2020
DOI: 10.1111/ppc.12683
|View full text |Cite
|
Sign up to set email alerts
|

Body perception and sexuality of bariatric surgery patients

Abstract: This study aims to determine how body perception and sexual life are affected in obese individuals who are hospitalized to undergo bariatric surgery. Design and Methods: Descriptive research design and the cross-sectional method were used. The study was conducted with 53 individuals who consented to participate. The data were analyzed with the SPSS software package.Findings: Low body perception and sexual dysfunction were detected, particularly in women.Practice Implications: In obesity treatment, the psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…However, it was observed that body image concerns were significantly higher in the group that had sexual dysfunction compared to the group that did not. This finding was evaluated as supportive of the study by Çaynak et al (28), which showed that body image had a significant effect on sexual life.…”
Section: Discussionsupporting
confidence: 84%
“…However, it was observed that body image concerns were significantly higher in the group that had sexual dysfunction compared to the group that did not. This finding was evaluated as supportive of the study by Çaynak et al (28), which showed that body image had a significant effect on sexual life.…”
Section: Discussionsupporting
confidence: 84%
“…Çaynak et al’s study, investigating the effects of body perception and sexual desires of bariatric surgery patients on obese individuals referred for bariatric surgery, indicated that BMI, height, and weight were not significantly related to sexual self-concept [ 28 ]. The result of this study is consistent with the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This deserves further scrutiny, as some issues related to these scales are clearly relevant to patients undergoing BS. 34,35 The NF was originally developed for patients receiving mental health treatment. Therefore, the high floor effects are likely a result of the population of patients undergoing BS having different characteristics and needs in treatment.…”
Section: Discussionmentioning
confidence: 99%